ACUTE MEGAKARYOBLASTIC LEUKEMIA - Ana Murtasyidah; Yulia Nadar Indrasari (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Acute Megakaryoblastic Leukemia (AMKL) is a subtype of acute myeloid leukemia triggered by megakaryocytes. Acute megakaryoblastic leukemia is divided into three groups, AMKL in children with Down syndrome (DS-AMKL), AMKL in children who do not have Down Syndrome (non-DS-AMKL), and AMKL in non-DS adults (AMKL adults).The basis of the diagnosis of AMKL or AML-M7, according to FAB, is the presence of megakaryocyte line cells as many as 30% or more of all cells. Meanwhile, the diagnosis of AMKL, according to the 2016 WHO guidelines, is acute leukemia with blasts, about > 20%, > 50% of which is megakaryocyte line cells. Megakaryocyte cells can be more clearly seen with electron microscopes that react positively to platelet peroxidase or use marker antibodies to CD41/gpIIb, CD42b/gpIb, CD61/gpIIIa, von Willebrand factors, and linker for T cell activation.Based on the results of this research, there are differences in cytogenetics between the three types of AMKL according to their different pathophysiology. The World Health Organization (WHO) argued that AMKL was categorized into not otherwise specific (NOS) AML criteria. These criteria exclude AML with myelodysplasia (AMLMRC), AML associated with therapy, and AML with recurrent genetic abnormalities, such as AML with t (1; 22) (p13.3; q13.1), inv (3) (q21.3q26.2), or t (3; 3) (q21.3; q26.2). DS-AMKL is also classified into myeloid leukemia associated with DS. In conclusion, AMKL in adults is not only considered as a rare subtype of AMKL, only 1% of AML cases in population-based clinical experiments and data but also has a poor prognosis.